Biological conversion of alkanes to dicarboxylic acids : an investigation into process challenges and optimisation in hydrocarbon-based bioprocesses - Williams, Peta Clair (Centre for Bioprocess Engineering Research, 2014)
The focus of this project is bioconversion of alkanes to dicarboxylic acids. Dicarboxylic acids are versatile chemical intermediates that can be used in the manufacture of perfumes, polymers, adhesives and antibiotics. The use of a hydrocarbon in a biological process, however, introduces several process challenges related to the nature of the substrate. Many of these challenges are common to all hydrocarbon fermentations, regardless of the product formed, and include flammability, volatility and inhibition of cell growth (notably at low carbon chain lengths), insolubility (notably at high carbon chain lengths) and mass transfer limitations, with respect to both oxygen and alkane substrate. In particular, the provision of adequate oxygen transfer to the organism in hydrocarbon-based bioprocesses has been regarded as especially challenging because of the absence of oxygen in the hydrocarbon backbone. In contrast to carbohydrate-based bioprocesses in which the carbohydrate itself supplies about half of the oxygen, the metabolic requirement for oxygen in hydrocarbon-based bioprocesses has to be met entirely by the transfer of oxygen to the broth. This suggests a proportionately higher requirement for oxygen transfer under these conditions. Consequently, the oxygen transfer rate (OTR) has been mooted as a likely major process limitation, leading to a process which is transport, rather than kinetically controlled and correspondingly, a sub-optimal yield and productivity.